The Effect of Performance Rating Systems on Employee Motivation of Nepalese Insurance Companies - Goet, Joginder; Kharel, Kiran (Dristikon: A Multidisciplinary Journal, 2023)
This study explores the effects of employee motivational elements, such as training and development (TD), communication (CO), commitment (CT), reward and recognition (RR), and feedback systems (FS) in listed insurance businesses in Nepal. The impact of motivational elements on employee motivation was investigated using the primary data from 405 observations of 24 Insurance Companies. This study examined the link and impact of the aforementioned elements on employee motivation in Nepalese insurance businesses using a correlational and causal research technique. This study identified a relationship between employee motivation (EM) and training and development (TD), communication (CO), commitment (CT), rewards and recognition (RR), and feedback systems (FS). Again, it has been discovered that Employee Motivation (EM) in Nepalese Insurance Companies is significantly influenced by Training and Development (TD), Communication (CO), Commitment (CT), Reward and Recognition (RR), and Feedback System (FS).